Computer-based comparison of different methods for selecting mitral annuloplasty ring size - Maisary, Sameer al-; Engelhardt, Sandy; Graser, Bastian; Wolf, Ivo; Karck, Matthias; De Simone, Raffaele (Journal of cardiothoracic surgery, 2017)
Ring sizing for mitral valve annuloplasty is conventionally done intraoperatively using specific ‘sizer’ instruments, which are placed onto the valve tissue. This approach is barely reproducible since different sizing strategies have been established among surgeons. The goal of this study is to virtually apply different sizing methods on the basis of pre-repair echocardiography to find out basic differences between sizing strategies.
Gesehen am 09.04.2018